2020
DOI: 10.1186/s43046-020-00025-5
|View full text |Cite
|
Sign up to set email alerts
|

Implications of the 21-gene recurrence score assay (Oncotype DX) on adjuvant treatment decisions in ER-positive early-stage breast cancer patients: experience of Kuwait Cancer Control Center

Abstract: Background: The Oncotype DX is a quantitative assay of the expression of 16 tumor-related genes and 5 reference genes that predicts the potential of adjuvant chemotherapy benefit in estrogen receptor (ER)-positive early breast cancer patients. The study aims to evaluate the impact of Oncotype DX as a tool for adjuvant treatment decision of ER-positive, HER2-negative, N0/N1 early-stage breast cancer patients and to determine which clinicopathological criteria derived the greatest advantage. Results: A hundred p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 17 publications
(17 reference statements)
4
6
0
Order By: Relevance
“…Studies have reported that the ODx RS does not only predict the RR but can also predict mortality independently of other covariates [11]. In line with our findings, a recent study also reported an impact of the assay on AC decision, leading to a change in the decision of omitting chemotherapy in 37% of the cases where chemotherapy was recommended pre-ODx, and in 14.8% of the cases where chemotherapy was prescribed after the decision was changed to yes to chemotherapy from an initial decision of a norecommendation [24]. Compared to our study they reported a higher percentage of patients with a change in the decision for both groups.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Studies have reported that the ODx RS does not only predict the RR but can also predict mortality independently of other covariates [11]. In line with our findings, a recent study also reported an impact of the assay on AC decision, leading to a change in the decision of omitting chemotherapy in 37% of the cases where chemotherapy was recommended pre-ODx, and in 14.8% of the cases where chemotherapy was prescribed after the decision was changed to yes to chemotherapy from an initial decision of a norecommendation [24]. Compared to our study they reported a higher percentage of patients with a change in the decision for both groups.…”
Section: Discussionsupporting
confidence: 90%
“…In other words, the change to a decision of chemotherapy administration was less frequent than the change to a decision of omitting chemotherapy. This is consistent with those reported in the region as well as internationally [1,24,25]. Rizki et al also reported that the precision of the ODx score in guiding the decision to use AC is much superior to other clinicopathological tools [26].…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations